Contemporary mass media and the communication of anthropogenic climate change in the Russian Federation - Poberezhskaya, Marianna (2013)
This thesis examines the media coverage of anthropogenic climate change in the Russian Federation. It achieves this aim by testing Edward S. Herman and Noam Chomsky's Propaganda Model (1988) which argues that media coverage predominately stays within the boundaries defined by the 'elite's' interests. Through media analysis as well as elite interviews, this project has found that in the Russian case, regardless of the newspapers' ownership structure or dependence on advertising, there is little difference in quantity and quality of overall coverage on climate change. Most newspapers rely on Russian officials as information sources, almost none criticize or question Russian climate change policy and Russia's contribution to global levels of greenhouse gas emissions. This subordinate media policy is not the result of any purposeful and overt state censorship or management of media activity on the issue of climate change, but the product of the media's 'genuine' interest in the state elites as the 'main newsmakers' on the problem and a 'genuine' public lack of interest in climate change as an issue. Furthermore, the study concludes that in the Russian case the omission of climate change issues from media discussions is a greater problem than biased coverage as it prevents the issue from entering public debates. However, considering media interest in the state and the recent change in state climate policy (by becoming more tolerant towards climate change mitigation measures) it is argued that coverage of climate change in Russia will steadily increase and in this case, media 'consent' with the elites' interests will eventually benefit the development of public and official discourse on the problem.